Childcare and parental work schedules: a comparison of childcare arrangements among Finnish, British and Dutch dual-earner families. Issue 3 (26th May 2016) - Verhoef, Melissa; Tammelin, Mia; May, Vanessa; Rönkä, Anna; Roeters, Anne
Abstract : This study examined the association between parental work schedules and non-parental childcare arrangements among dual-earner families in Finland, the Netherlands and the UK. Data from the 'Families 24/7' web survey were used, including 937 parents with children aged 0–12 years. Results showed a negative association between non-standard work and formal childcare across all countries. A similar association was found for using a combination of formal and informal childcare, whereas solely using informal childcare was not associated with work characteristics. Country differences showed that, compared with Finland, the probability of using formal childcare was lower in the Netherlands, whereas the probability of using informal childcare was higher in the UK. Interaction effects showed that the negative association between non-standard work and formal childcare was stronger in the Netherlands, compared with Finland. Also, the positive association between working hours and formal childcare was weaker for Dutch and British parents. This study identified the challenges that parents face when arranging childcare outside of office hours. Although the supply of formal childcare seems to be insufficient, using informal childcare introduces other potential problems. Because a considerable proportion of employees work non-standard hours, governments should help these parents in meeting their need for high quality childcare.